Kinematics and Dynamics Model of GH4169 Alloy for Thermal Deformation - WANG, Zhong-tang; ZHANG, Shi-hong; CHENG, Ming; LI, De-fu; YANG, Xiao-hong (Journal of iron and steel research, international, 2010)
The stress-strain curves and microstructure properties of superalloy GH4169 was tested by thermal simulation experiment with different parameters,which were deformation temperature and strain rate and strain and original grain size.The influence of technology parameters on crystal grain size of dynamic recrystallization（DRC）was analyzed.The kinematics model of superalloy GH4169 was established,in which the relation between grain size of dynamic recrystallization and function Z（Zener-Hollomon）and parameters was described.The dynamics model of superalloy GH4169 was put forward,which described the relation between the quantity of dynamic recrystallization and function Z and parameters.The research results showed that the grain size of dynamic recrystallization increased with increasing the temperature and decreasing the strain rate.And the grain size of DRC bore no relationship to original grain size.And the quantity of dynamic recrystallization decreased with increasing the original grain size.